MORFOLOGI BAHASA DAYAK MALI DIALEK PERUAN DI KECAMATAN TAYAN HULU - Hardianita, Desia; Salem, Laurensius; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The native speakers of it, spread out around Tayan Hulu District, Sanggau The problem of this research is the affix of Dayaknese of Mali in Peruan Dialect,in which limited to become 3 subtitles of problem, such as pattern, function and meaningful. The research used is the descriptive methode. The resources of the data in the research is BDMDP which is spoken by the community of Dayaknese of Mali in Peruan Dialect, in Kecamatan Tayan Hulu. The Data of this research is the affix of Dayaknese of Mali in Peruan Dialect,in the words spoken by the community of Dayaknese of Mali in Peruan Dialect, in Kecamatan Tayan Hulu. The technich used in the research, is teknik libat cakap (active conversation technic), showing picture technic, interview technic, and documentation study technic. The affix of BDMDP consist of 5 patterns, such as : N-, ber-, poN-, ter-, do The pattern of prefix N- has some patterns of variation, such as m-, n-, Ƞ-, Ƞc-, dan zero. The prefixs ber-, b-, be-, and bel-. The allomorph of prefixs ter- such as : ter- and te-, while prefixs do- in BDMDP does not have any pattern of variation when it is arranged in free morpheme as well. Keywords: Morphology, Dayaknese of Mali, Peruan Dialex